2019
DOI: 10.1002/ijc.32261
|View full text |Cite
|
Sign up to set email alerts
|

AMPK variant, a candidate of novel predictor for chemotherapy in metastatic colorectal cancer: A meta‐analysis using TRIBE, MAVERICC and FIRE3

Abstract: AMP‐activated protein kinase (AMPK) is a key sensor of energy homeostasis and regulates cell metabolism, proliferation and chemotherapy/radiotherapy sensitivities. This study aimed to explore the relationship between the AMPK pathway‐related single nucleotide polymorphisms (SNPs) and clinical outcomes in patients with metastatic colorectal cancer (mCRC). We analyzed a total of 884 patients with mCRC enrolled in three randomized clinical trials (TRIBE, MAVERICC and FIRE‐3: where patients were treated with FOLFI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…The imputation panel reported in the prior CORECT study was updated to the 1000 Genomes Project Phase 3. 22 Seventeen candidate SNPs of genes in FAs uptake ( CD36 rs1761667, rs7755, rs1194197; FABP4 rs1054135, rs16909187, rs2290201), lipid synthesis ( FASN rs4246444, rs4485435, rs6502051; ACACA rs7211875, rs1714987), FAO ( CPT1A rs2278908, rs11228373) and phosphatidylcholine remodeling ( LPCAT1 rs7737692; LPCAT2 rs9302667, rs893260, rs837550) were selected using the following criteria as previously described 23 ( Table S1 ): (1) MAF in Caucasians should be equal or greater than 10%, based on Ensemble Genome Browser ( https://www.ensembl.org/index.html ). (2) SNPs with potential biological functions based on published papers or public databases (snpinfo.niehs.nih.gov/snpinfo/snpfunc.html).…”
Section: Methodsmentioning
confidence: 99%
“…The imputation panel reported in the prior CORECT study was updated to the 1000 Genomes Project Phase 3. 22 Seventeen candidate SNPs of genes in FAs uptake ( CD36 rs1761667, rs7755, rs1194197; FABP4 rs1054135, rs16909187, rs2290201), lipid synthesis ( FASN rs4246444, rs4485435, rs6502051; ACACA rs7211875, rs1714987), FAO ( CPT1A rs2278908, rs11228373) and phosphatidylcholine remodeling ( LPCAT1 rs7737692; LPCAT2 rs9302667, rs893260, rs837550) were selected using the following criteria as previously described 23 ( Table S1 ): (1) MAF in Caucasians should be equal or greater than 10%, based on Ensemble Genome Browser ( https://www.ensembl.org/index.html ). (2) SNPs with potential biological functions based on published papers or public databases (snpinfo.niehs.nih.gov/snpinfo/snpfunc.html).…”
Section: Methodsmentioning
confidence: 99%
“…AMPK is a conservative Ser/Thr protein kinase, which regulates cell metabolism and maintains the dynamic balance of cell metabolism, thus it is referred to as a regulator of energy homeostasis ( Faubert et al, 2013 ; Narayanankutty, 2019 ). AMPK is activated by sensing the increase of AMP and ATP ( Tokunaga et al, 2019 ). Once activated, AMPK will immediately block the energy consumption process of cells, and turn to increase the ATP decomposition process ( Wang and Guan, 2009 ).…”
Section: Aerobic Glycolysis In Crcmentioning
confidence: 99%
“…It has been shown that AMPK, which plays a key role in cellular energy homeostasis, contributes positively to these results with its modulation at high bilirubin levels (14). In addition, it is known that the AMPK pathway is activated by ionizing radiation, and AMPK activation is associated with a good prognosis in breast (20) and colorectal carcinoma (21). In the in-vitro study on breast cancer, it has been proven that metformin, which acts with the activation of the AMPK pathway and is evaluated as an antineoplastic agent, increases radiosensitivity by affecting intracellular reactive oxygen radicals (ROS) (20).…”
Section: A B Cmentioning
confidence: 99%